Demographic and clinical characteristics of free-text writers in chronic pain patient intake questionnaires. Issue 1 (31st December 2022) - Roy, Rachel; Sommer, Jordana L.; Amadeo, Ryan; Reynolds, Kristin; Kilborn, Kayla; Sabourin, Brigitte; El-Gabalawy, Renée
ABSTRACT: Background: Chronic pain is a prevalent and burdensome problem within the Canadian health care system, where the gold standard treatment occurs at multidisciplinary pain facilities. Patient intake questionnaires (PIQs) are standard practice for obtaining health information, with many patients including free-text (e.g., writing in margins of questionnaires) on their PIQs. Aims: This study aims to quantitatively examine whether and how patients who include free-text on PIQs differ from those who do not. Methods: We retrospectively analyzed 367 PIQs at a Canadian pain facility in Winnipeg, Canada. Patients were categorized into free-text (i.e., any text response not required in responding to questions) or no free-text groups. Groups were compared on sociodemographics, pain, health care utilization, and depressive symptoms with independent samples t -tests and chi-square analyses. Results: Patients with free-text compared to those without had more sources of pain (6.66 vs. 4.63), longer duration of pain (123.2 months vs. 68.1 months), and a greater proportion of past pain conditions (66.3% vs. 55.2%). Additionally, they had tried more treatments for their pain, had seen more specialists, had tried more past medications, were currently on more medications, and had undergone more tests. No differences were identified for depressive symptoms across groups. Conclusions: This study is the first to examine patient and health-related correlates of free-text on PIQs at a Canadian pain facility. Results indicate that there are significant differences between groups on pain and health care utilization. Thus, patients using free-text may require additional supports and targeted interventions to improve patient–physician communication and patient outcomes.